Broadening the focus of evaluation: An experiment - Subrata Chakraborty; Shailja Agarwal (International Journal of Business Science & Applied Management (IJBSAM), 2010)
Evaluation of student performance in any course, especially those delivered in a management programme, poses a serious challenge; more so, in a course like "Business Communication", where oral communication ought to form an integral part of evaluation. This paper presents various details of an experiment, conducte d with a view to introduce this much needed component in the evaluation process. Essential purpose of the exercise was to try and broaden the focus of evaluation, simultaneously enlarging its scope. The need to maintain certain amount of objectivity and tr ansparency was taken as critical. Group Discussion was used as a tool. A process was developed with the objective of getting every student evaluated on both written as well as non - written skills. A two - sided evaluation mechanism was put in place to achieve the dual purpose of leaning and evaluation. Statistical analysis of the results suggests that the experiment was a useful one. The student feedback, too, was favourable.
Keywords: 650; business communication; non-written skills; written skills; group discussion; evaluation